2021
DOI: 10.3390/educsci11080407
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Teachers Self-Perception of Digital Teaching Competence in Spain Following COVID-19 Confinement

Abstract: The education system has become even more complex following the global pandemic, which saw face-to-face teaching transition to virtual teaching. To cope with this abrupt transition, it is essential that teachers have a sufficient level of digital teaching competence. This article aims to increase awareness of teachers’ self-perception of their digital teaching competences in the educational field. Specifically, this study explores Spanish secondary school teachers’ knowledge and use of different ICT tools by e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
20
0
3
Order By: Relevance
“…-Tener en cuenta factores que afectan en los resultados: factores sociodemográficos, como el género (Esteve-Mon et al, 2020a), los años de experiencia docente (Zhao, 2021), la edad o el nivel educativo (Flores-Lueg & Roig-Vila, 2019), y factores estructurales, como la dotación de recursos o las oportunidades formativas de los docentes (Cattaneo et al, 2022). -Ampliar el tamaño de las muestras y los contextos geográficos en los que se recogen datos para poder comparar resultados (Jorge-Vázquez, 2021;Prieto Ballester et al, 2021).…”
Section: áMbito De Investigación 3 Análisis De Los Resultados De La E...unclassified
See 1 more Smart Citation
“…-Tener en cuenta factores que afectan en los resultados: factores sociodemográficos, como el género (Esteve-Mon et al, 2020a), los años de experiencia docente (Zhao, 2021), la edad o el nivel educativo (Flores-Lueg & Roig-Vila, 2019), y factores estructurales, como la dotación de recursos o las oportunidades formativas de los docentes (Cattaneo et al, 2022). -Ampliar el tamaño de las muestras y los contextos geográficos en los que se recogen datos para poder comparar resultados (Jorge-Vázquez, 2021;Prieto Ballester et al, 2021).…”
Section: áMbito De Investigación 3 Análisis De Los Resultados De La E...unclassified
“…En respuesta a la P5 sobre las peculiaridades de las herramientas empleadas para evaluar la CDD, respecto a los tipos de herramientas y técnicas de recogida de información que se utilizan, se encontró que en el 89.39% de los estudios fue un cuestionario de autopercepción de la CDD. Tres estudios utilizaron un enfoque mixto, combinando el cuestionario con los grupos de discusión (Llopis Nevot et al, 2021;Ruiz Cabezas et al, 2020) y también con las entrevistas, el análisis documental y la observación sistemática (Prieto-Ballester et al, 2021). Dos estudios cualitativos utilizan la entrevista (Suárez Guerrero et al, 2021) y en uno de ellos además realizaron grupos de discusión (Sales et al, 2020).…”
Section: áMbito De Investigación 2 Descripción De Los Métodos De Inve...unclassified
“…Although communication between administrative officers and students is an element of satisfaction in educational systems with reduced attendance [3], the role of lecturers compensated for this lack of communication. Lecturers were a key element in the process of adapting to the educational system imposed during the pandemic [5,18]. McKenzie et al [52] found that establishing direct communication channels between lecturers and students helped maintain their trust.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining timely feedback from lecturers in the evaluation process was crucial for students during online education in the pandemic period [15][16][17]. Furthermore, Flores et al [5] and Prieto-Ballester et al [18], showed that the level of digital literacy for online communication during confinement directly and positively affected students' well-being in online classes. In other words, HE requires quality organizational measures in the face of the change caused by COVID-19 [15,19,20].…”
Section: Communication In He In the Pandemic Period: Literature Reviewmentioning
confidence: 99%
“…However, the COVID-19 crisis is the consequence of a rise in the number of infections that are repeated in second or third waves. Unfortunately, we are now witnessing new waves of coronavirus and its impacts in different countries, e.g., Spain [4,5], Germany [6,7], Australia [8], Italy [9,10], Japan [2], Singapore [11], Malaysia [12], India [13], South Africa [14], Norway [15], Sweden [16], Pakistan [17], and The Philippines [18], to name a few. No-one knows where the pandemic will lead us and when the pandemic and the consequent crisis will finish in the world.…”
Section: Introductionmentioning
confidence: 99%